Introducing Tana Toraja: Icon of Religious Moderation on the World Stage Through Cultural Customs - Bariyah, Choerul; Hardiyantia, Silvira; Saputra, Nafar; A. Nuranisya, A. Nuranisya; Aqil, M. Sayyid; Dahniel, Muh; Fitriana S, Risyah; Taula Bi’, Duma’; Khoiri, Mahfuz; Askur, Muhammad; Imro’atul F, Khanana (Dharmahita: Journal of Community Service and Development, 2024)
This study aims to describe and implement the religious harmony that originates from the customs of Tana Toraja, South Sulawesi. The research focuses on the diverse religious and cultural practices in Tana Toraja, particularly in the Lembang Pakala area, RT. Tarangga. The findings highlight the community's longstanding embrace of religious and cultural diversity, exemplified by customs such as Rambu Solo, a funeral ceremony, and practices promoting religious tolerance, like providing food to Christian children in schools and avoiding pork offerings to Muslims. The study suggests that these customs not only foster religious harmony locally but also serve as a model for other regions in Indonesia. The cultural practices of Tana Toraja demonstrate how to build a sense of togetherness and harmony among diverse religious communities, extending beyond just Muslims and Christians. This research underscores the potential for these customs to contribute to broader efforts in promoting religious moderation and unity on a global scale.